Specialized Languages - Birthe Mousten; Anne Lise Laursen (Akademisk Kvarter, 2016)
Across different fields of research, one feature is often overlooked: the use of language for specialized purposes (LSP) as a cross-discipline. Mastering cross-disciplinarity is the precondition for communicating detailed results within any field. Researchers in specialized languages work cross-disciplinarily, because they work with both derivative and contributory approaches. Derivative, because specialized language retrieves its philosophy of science as well as methods from both the natural sciences, social sciences and humanistic sciences. Contributory because language results support the communication of other sciences. Take for instance computational linguistics: its derivative part uses the competences and methods from computer science and couples them with linguistics; its contributory part is the lexicographical, terminological and syntactical results within a specific domain or genre that help science fields communicate their findings. With this article, we want to create awareness of the work in this special area of language studies and of the inherent cross-disciplinarity that makes LSP special compared to common-core language. An acknowledgement of the importance of this field both in terms of more empirical studies and in terms of a greater application of the results would give language specialists in trade and industry a solid and updated basis for communication and language use.